1992
DOI: 10.1207/s15327752jpa5902_13
|View full text |Cite
|
Sign up to set email alerts
|

Three Loneliness Scales: An Assessment of Thier Measurement Properties

Abstract: In loneliness research, there has not been a consensus concerning either the factorial structure of most loneliness scales or the factorial structure of each of the proposed dimensions of loneliness. We investigated theoretical and operational definitions, as well as the factorial structure, based on gender of three loneliness scales: the University of California at Los Angeles (UCLA) Loneliness Scale, the Loneliness Deprivation Scale, and the Emotional/Social Loneliness Inventory. Unidimensional, best-fit mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 43 publications
2
31
1
1
Order By: Relevance
“…A well-established measure is the revised version of the UCLA Loneliness Scale (UCLA-R; Russell, Peplau, & Cutrona, 1980), which has been used in an estimated 80% of all empirical studies on loneliness (Oshagan & Allen, 1992). Two types of items can be found in the scale, which probe for (a) negative appraisals of one's social relationships and (b) the negative emotions, most notably the feeling of being abandoned, that accompany such appraisals (Shaver & Brennan, 1991).…”
Section: Measuring Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established measure is the revised version of the UCLA Loneliness Scale (UCLA-R; Russell, Peplau, & Cutrona, 1980), which has been used in an estimated 80% of all empirical studies on loneliness (Oshagan & Allen, 1992). Two types of items can be found in the scale, which probe for (a) negative appraisals of one's social relationships and (b) the negative emotions, most notably the feeling of being abandoned, that accompany such appraisals (Shaver & Brennan, 1991).…”
Section: Measuring Lonelinessmentioning
confidence: 99%
“…Most of the other short forms were developed on samples of college students (e.g., Hays & DiMatteo, 1987;Wu & Yao, 2008) or adults (e.g., Oshagan & Allen, 1992). Second, the RULS-8 is a balanced scale in terms of item valence (i.e., positive vs. negative wording), whereas other brief versions comprise mostly (Hays & DiMatteo, 1987;Wu & Yao, 2008) or exclusively negatively worded items (Hughes et al, 2004;Oshagan & Allen, 1992). Exploratory factor analysis and conceptual analysis further indicate that the developers of the RULS-8 managed to preserve much of the content coverage of the full-length measure.…”
Section: The Roberts Version Of the Ucla Loneliness Scale (Ruls-8)mentioning
confidence: 99%
“…Most people are probably going to have a significant experience of loneliness some time in their lives (Rokach & Brock, 1997). Oshagan and Allen (1992) reported that the prevalence of loneliness in the general population has been estimated to range from 15% to 28%. Unfortunately, researchers emphasized that loneliness is a more prevalent and serious problem among university students.…”
Section: Lonelinessmentioning
confidence: 99%
“…Obviously, every one of us has the experience of feeling lonely at certain points in our lives (Asher & Paquette, 2003;Rokach & Brock, 1997). The prevalence rate of loneliness in the general population is about 20% to 28% (Cacioppo & Patrick, 2008;Oshagan & Allen, 1992). From being an adolescent to being an adult and as a transitional period from high school to college, it is no wonder that college students are haunted by loneliness (Cutrona, 1982;O'Donovan & Hughes, 2007;Vanhalst, 2012).…”
Section: Introductionmentioning
confidence: 99%